“My Child Might Be Thinking About Something Beneficial to Humanity”: Enhancing Parental Perspectives on Engineering Education in Early Childhood - Ata-Aktürk, Aysun; Demircan, H. Özlen (Informa UK Limited, 2024)
This qualitative case study explores how parental involvement (PI) in early engineering education (EEE) of 5- to 6-year-old children provided through a school-based program reflected on Turkish parents' perspectives regarding three themes: 1) engineering, 2) EEE, and 3) PI in EEE. Data were collected from 13 parents through pre- and post-interviews and reflective journals. Findings revealed that, after their involvement in the program activities, parents tended to define engineering as related to problem-solving and facilitating daily life and perceive the contributions of EEE to children more comprehensively. After participating in the program, parents reported a more expanded perception of alternative ways of supporting their children's EEE through PI. Findings also indicated that parents' perceived life contexts might constitute a barrier to PI in EEE, and parents need more guidance on providing effective scaffolding for their children's EEE.